Where Do Human Capital Externalities End Up To? - Alberto Dalmazzo; Guido De Blasio (European Regional Science Association (ERSA), 2005)
Recent literature has aimed at evaluating human capital externalities by estimating the effect of human capital on wages at urban level. We argue that this methodology might not identify properly human capital spillovers. We consider a general equilibrium model based on Roback (1982) where both wages and rents are simultaneously determined at the local level. We show that human capital externalities cannot be identified unless the joint effect of local human capital on both wages and rents is considered. Empirically, we study the effects of local human capital on household-level rents and individual-level wages for a sample of Italian local labor markets. Our results show a positive and robust effect of local human capital on rents. This unambiguously demonstrates that the concentration of human capital at the local level generates positive externalities. As for the relative importance of consumption and production externalities, our results suggest that the two effects have a similar impact on wages.
Keywords: 330